Dosimetry of external population exposure: a comparison of the Chernobyl and Fukushima accidents - V. Yu. Golikov (Радиационная гигиена)
The paper is devoted to comparing the models and the doses of the population external exposure from radioactive fallout after the accident at the Chernobyl and Fukushima-1 NPPs estimated with their help. In the case of the Fukushima-1 accident, the model proposed by the UNSCEAR was used. Both the values of the doses of gamma radiation in the environment and the values of the effective doses of external exposure of comparable population groups normalized to the same surface activity of radionuclides were close for both accidents. The reasons for this are both the similarity of the isotopic compositions of the radioactive fallout and the fact that the “Japanese” model of external exposure was based on the “Chernobyl” model up to using the same numerical values for some parameters, due to the lack of specific Japanese post-accident data for the moment of the first dose estimates for the inhabitants of Japan. For a more accurate comparison of the external exposure of residents after two accidents it is necessary to verify the values of the parameters of the Japanese model using the results of measurements of gamma radiation dose rates in the environment and individual external doses of the residents after the accident at the Fukushima-1 NPP.